Abundance estimates and trends for humpback whales (Megaptera novaeangliae) in Antarctic Areas IV and V based on JARPA sightings data - Matsuoka, Koji; Hakamada, Takashi; Kiwada, Hiroshi; Murase, Hiroto; Nishiwaki, Shigetoshi (J. Cetacean Res. Manage., 2020)
Sighting survey data from the Japanese Whale Research Program under Special Permit in the Antarctic (JARPA) are analysed to obtain abundance estimates for humpback whales (Megaptera novaeangliae) south of 60°S. The surveys were conducted during the 1989/90–2004/05 austral summer seasons (mainly in January and February); the survey areas alternated between Area IV (70°E–130°E) and Area V (130°E to 170°W) each year. Primary sighting effort totalled 293,811 n.miles over 6,188 days. Abundance estimates are obtained using standard line transect analysis methods and the program DISTANCE. Estimated densities of humpback whales were highest east of the Kerguelen Plateau (80°E–120°E). Abundance estimates for Area IV range from 2,747 (CV = 0.153) in 1993/94 to 31,134 (CV = 0.123) in 2001/02, while those for Area V range from 602 (CV = 0.343) in 1990/91 to 9,342 (CV = 0.337) in 2004/05. The estimates are similar to those obtained from the International Whaling Commission’s IDCR-SOWER surveys, which were conducted in Area IV (in 1978/79, 1988/89 and 1998/99) and in Area V (in 1980/81, 1991/92 and 2001/02– 2003/04). Estimated annual rates of increase for Area IV (16.4%; 95% CI = 9.5–23.3%) and Area V (12.1%; 95% CI = 1.7–22.6%) are also similar to those obtained from the IDCR-SOWER surveys. The total abundance in Areas IV and V based on the most recent JARPA surveys (2003/04 and 2004/05 combined) is 37,125 (95% CI = 21,349–64,558); the confidence interval incorporates estimated additional variance. Results of several sensitivity tests are presented that suggest that estimates of abundance and trends are not appreciably affected by factors such as different approaches to deal with survey coverage (which in some cases was poor or included gaps). Changes in the order in which survey strata were covered and potential effects are investigated using a nested GLM approach; a QAIC model selection criterion suggests a preference for not attempting to adjust for such changes. Under various sensitivity approaches, the point estimates of increase rates are not greatly affected for Area IV. Although they drop by typically a half for most approaches for Area V, they nevertheless remain within the confidence limits of the base case estimate of 12.1% per year (95% CI = 1.7–22.6%). The presented results thus suggest that the estimated abundance of humpback whales in Area IV has increased rapidly. Although there is also an increase indicated for Area V, it is neither as rapid nor as precisely estimated. Taking these results together with the similar rates of increase estimated from coastal surveys off western and eastern Australia for Breeding Stocks D and E respectively, and given demographic limitations on the increase rates possible for closed populations of humpback whales, the hypothesis is advanced that whales from Breeding Stock E may have shifted their feeding distribution westward as their numbers have increased, perhaps to take advantage of the higher densities of krill to be found to the west.